Dyslipidemia is Associated with Coronary Heart Disease in Patients with Type 2 Diabetes Mellitus at a Tertiary Hospital in Surabaya, Indonesia - Ramadhani, Rizqi Nabila; Humairah, Ira; Novida, Hermina; Qurnianingsih, Ema (Universitas Airlangga, 2025)
Introduction: Diabetes mellitus ranks as the third leading cause of mortality in Indonesia. The commonly found comorbidity of diabetes mellitus is cardiovascular disease, which contributes to elevated mortality rates. Diabetes mellitus sufferers face a heightened risk of cardiovascular disease, in part, due to dyslipidemia. This study aimed to establish the association between dyslipidemia and coronary heart disease (CHD) in type 2 diabetes mellitus (T2DM) patients receiving treatment at the diabetes subdivision of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This retrospective cross-sectional investigation examined 100 eligible individuals with T2DM and dyslipidemia at the diabetes subdivision of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, to assess the prevalence of CHD. Statistical analysis was performed using Pearson's chi-squared test to determine whether there was an association between dyslipidemia and CHD in the T2DM sufferers. If the p-value was below 0.05, the findings of the analysis were considered significant. The statistical test was conducted through IBM SPSS Statistics for Windows, version 26.0 (IBM Corp., Armonk, N.Y., USA). Results: Dyslipidemia was present in 74% of the T2DM patients. Patients who had dyslipidemia and T2DM were primarily female and aged between 51 and 60 years. Meanwhile, CHD affected 40 T2DM patients (40%). These patients were predominantly male and between the ages of 51 and 60. T2DM patients who also suffered from CHD typically presented with dyslipidemia (85%). Conclusion: This study demonstrates that the presence of dyslipidemia in T2DM sufferers is associated with CHD. Highlights: 1. This study examined type 2 diabetes mellitus patients receiving treatment in a tertiary hospital to determine the association between dyslipidemia and coronary heart disease, an important concern given the rising prevalence of the disease in Indonesia. 2. The analysis revealed that type 2 diabetes mellitus patients who also have dyslipidemia face an elevated risk of developing coronary heart disease. 3. This study offers additional information, particularly related to the presence of dyslipidemia and coronary heart disease, which may enhance the management of type 2 diabetes mellitus throughout primary, secondary, and tertiary health facilities.